Overview and Comparison of Physical and Chemical Methods to Produce Cu-Ag Nanoparticles - Inzamam Khalid (Physics Department, Faculty of Mathematics and Natural Sciences, University of Jember, 2023)
The present article deals with the overview of methods to produce Ag-Cu nanoparticles. Different chemical and physical procedures for the preparation of Ag-Cu nanoparticles are presented. A simple chemical reduction method is used to synthesise the colloidal mixture of bimetallic Ag-Cu nanoparticles. The Ag-Cu nanoparticles can be further characterised by powder X-ray diffraction (XRD), transmission electron microscopy (TEM), and UV–spectra. In physical techniques for the production of nanoparticles, laser ablation is used to produce Ag-Cu nanoparticles in alloy form. The analytical study can be done using characterisation techniques like SEM, HRTEM, SERS, and UV-visible spectroscopy.Keywords: Ag-Cu nanoparticles, XRD, Physical methods, Chemical methods, TEM, SEM.